Input-output Linearizing Control of Strong Acid-base Neutralization Process with Fluctuation in Feed pH - Srihawan, Thana; Panjapornpon, Chanin (Applied Science and Engineering Progress, 2020)
This work presents a control system design for coupled control of pH and level with fluctuation in influent pH by manipulating influent and acid flow rates. A mathematical model based on the difference between proton and hydroxide ions estimated by the measured pH is introduced and applied in a formulation of the model-based control system. A feedback controller and estimated state disturbance are obtained by solving a minimization problem of squared errors between requesting input-output linearizing output responses and the reference setpoints. To eliminate the offset response, the estimated disturbance is applied in the calculation of the closed-loop compensator. The performance of the developed control system is evaluated in a bench-scale pH neutralization process of HCl-NaOH system, and it is also compared to that of a proportional-integral controller. The results show that the developed controllers could enforce a system with fluctuation in influent pH to the desired setpoints effectively, while the PI controller gave oscillation in outputs around the setpoints and cannot achieve the desired targets.